Reforming specialized inspection procedures to improve business environment in Vietnam for trade facilitation implementation - Nga Le Thi Viet; Huy Dinh Tran Ngoc; Hang Nga Nguyen Thi; Lan Leng Thi; Thach Nguyen Ngoc (Zielona Góra: Faculty of Economics and Management Press)
Our study aims to analyze and assess the process of reforming the specialized inspection procedures in Vietnam which is included in Vietnam`s trade facilitation implementation program, and suggesting some recommendations for Vietnam to do the reform to improve business environment and enhance Vietnam`s national competitiveness.
Keywords: Vietnam; trade facilitation; inspection procedures; competitiveness; business environment; Wietnam; ułatwienia w handlu; handel; procedury kontrolne; konkurencja; środowisko biznesowe